Beyond the global brain differences: intraindividual variability differences in 1q21.1 distal and 15q11.2 BP1-BP2 deletion carriers - Bøen, Rune; Kaufmann, Tobias; van der Meer, Dennis; Frei, Oleksandr; Agartz, Ingrid; Ames, David; Andersson, Micael; Armstrong, Nicola J.; Artiges, Eric; Atkins, Joshua R.; Bauer, Jochen; Benedetti, Francesco; et al. (Biological psychiatry, 2024)
Background - Carriers of the 1q21.1 distal and 15q11.2 BP1-BP2 copy number variants exhibit regional and global brain differences compared with noncarriers. However, interpreting regional differences is challenging if a global difference drives the regional brain differences. Intraindividual variability measures can be used to test for regional differences beyond global differences in brain structure. - Methods - Magnetic resonance imaging data were used to obtain regional brain values for 1q21.1 distal deletion (n = 30) and duplication (n = 27) and 15q11.2 BP1-BP2 deletion (n = 170) and duplication (n = 243) carriers and matched noncarriers (n = 2350). Regional intra-deviation scores, i.e., the standardized difference between an individual’s regional difference and global difference, were used to test for regional differences that diverge from the global difference. - Results - For the 1q21.1 distal deletion carriers, cortical surface area for regions in the medial visual cortex, posterior cingulate, and temporal pole differed less and regions in the prefrontal and superior temporal cortex differed more than the global difference in cortical surface area. For the 15q11.2 BP1-BP2 deletion carriers, cortical thickness in regions in the medial visual cortex, auditory cortex, and temporal pole differed less and the prefrontal and somatosensory cortex differed more than the global difference in cortical thickness. - Conclusions - We find evidence for regional effects beyond differences in global brain measures in 1q21.1 distal and 15q11.2 BP1-BP2 copy number variants. The results provide new insight into brain profiling of the 1q21.1 distal and 15q11.2 BP1-BP2 copy number variants, with the potential to increase understanding of the mechanisms involved in altered neurodevelopment.
Gesehen am 08.04.2024